The Bactericidal and Antibiofilm Activity of Stem Bark of Jatropha multifida L. Against Staphylococcus aureus and MRSA - Annisa Fitria (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Chronical wound often caused by bacteria which has antibiotic resistance characteristic and presence of biofilm formation. This study aims to evaluate the bactericidal and antibiofilm activity of stem bark of Jatropha multifida L. against Staphylococcus aureus and MRSA (Methicillin-Resistant Staphylococcus aureus), as alternative antimicrobial agents. Examination of bactericidal activity of the extract was performed by time-kill assay to determine the speed of the extract to eradicate bacteria. The inhibitory activity of extract toward biofilm production was quantified using spectrophotometric method. The extract showed bactericidal activity which can be achieved at 8 hours and 12 hours against Staphylococcus aureus and MRSA in MBC value of 0.5 mg/mL and 1 mg/mL. The extract exhibited antibiofilm activity which indicates by its IC50 value of 0.3 mg/mL and 0.76 mg/mL against Staphylococcus aureus and MRSA. These experiments have shown the potential of the extract of Jatropha multifida L. stem bark as a bioactive substance in a topical agent for chronical skin infection.